2020
DOI: 10.1130/g48149.1
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the First Bend in the late Eocene gave birth to the modern Yangtze River, China

Abstract: The First Bend on the Yangtze River (China), the point where the river ceases flowing toward the south and heads toward the northeast, has been one of the most strongly debated geomorphic features in Asia because it holds the key to understanding the history of the Yangtze River and is linked to the tectonically driven surface uplift of the southeastern Tibetan Plateau. Mid- to upper Eocene sedimentary rocks preserved in the Jianchuan Basin located immediately southwest of the First Bend demonstrate that a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 25 publications
7
78
1
Order By: Relevance
“…The timing and the mechanism of the formation of the “First Bend” has always been controversial. The age of the “First Bend” has been suggested to range from Eocene (Richardson et al., 2010; Zheng et al., 2020), or the Oligocene‐Miocene (Clift et al., 2020; Chen et al., 2017; Yan et al., 2012), to the Pleistocene (Kong et al., 2009, 2012). In recent years, based on the “source to sink” research strategy, sediment provenance analyses including heavy mineral assemblages, major and trace element compositions, Sr‐Nd isotope ratios and detrital zircon U‐Pb ages have been widely used to discuss the river's evolution, chemical weathering, tectonic setting, and paleoenvironment (Alizai et al., 2011; Amidon et al., 2005; Condie & Wronkiewicz, 1990; He et al., 2014; Iizuka et al., 2005; Roddaz et al., 2006; Safonova et al., 2010; Singh, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The timing and the mechanism of the formation of the “First Bend” has always been controversial. The age of the “First Bend” has been suggested to range from Eocene (Richardson et al., 2010; Zheng et al., 2020), or the Oligocene‐Miocene (Clift et al., 2020; Chen et al., 2017; Yan et al., 2012), to the Pleistocene (Kong et al., 2009, 2012). In recent years, based on the “source to sink” research strategy, sediment provenance analyses including heavy mineral assemblages, major and trace element compositions, Sr‐Nd isotope ratios and detrital zircon U‐Pb ages have been widely used to discuss the river's evolution, chemical weathering, tectonic setting, and paleoenvironment (Alizai et al., 2011; Amidon et al., 2005; Condie & Wronkiewicz, 1990; He et al., 2014; Iizuka et al., 2005; Roddaz et al., 2006; Safonova et al., 2010; Singh, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Incision of the gorge in the First Bend area started between 20 and 30 Ma based on bedrock apatite (U-Th-Sm)/He thermochronology (31). Recently, studies using 40 Ar/ 39 Ar mica dating and zircon U-Pb dating methods coupled with statistical analysis suggest that a major Paleogene river probably originated in the southeastern Qinghai-Tibetan Plateau and owed through the Jianchuan Basin, extending to northern Vietnam during the late Eocene-Oligocene period, but disappearing by the early Miocene (32,33). Biological evidence from a time-calibrated phylogeny of only one sh genus (34)(35)(36) showed that the dating of the south-owing palaeo-Jinshajiang is younger than that predicted in this study by using the endemic East Asian Cyprinidae.…”
Section: Resultsmentioning
confidence: 99%
“…Combined with palaeontological evidence (39), we infer that the palaeo-elevation of the central Qinghai-Tibet Plateau was fairly low in the Oligocene, may not above 2000 m a.s.l. During the Eocene, reorganization of rivers did not occur because the southeastern part of the plateau was not uplifted signi cantly until the Oligocene (32). At the same time, southern East Asia was in a humid belt, while a broad arid belt stretched across central East Asia from west to east (1,40).…”
Section: Resultsmentioning
confidence: 99%
“…The age of the river incision located at Laojunshan near the rst bend of the Yangtze River from 20 to 30 Ma was determined by bedrock apatite (U-Th-Sm)/He thermochronology (31), and this age was close to the dating of the palaeo-Jinshajiang owing southward speculated in this study. Recently, studies using 40 Ar/ 39 Ar dating and zircon U-Pb dating methods and statistical analysis suggested that a major Paleogene river probably originated in the southeastern Qinghai-Tibet Plateau and owed through the Jianchuan Basin, extending to northern Vietnam during the late Eocene-Oligocene period, but disappearing by the early Miocene (32,33). Biological evidence from a time-calibrated phylogeny of only one sh genus (34)(35)(36) showed that the dating of the south-owing palaeo-Jinshajiang is younger than that predicted in this study by using the endemic East Asian Cyprinidae.…”
Section: The Palaeo-jinshajiang Owing Southward In the Oligocenementioning
confidence: 99%